Mechanisms of chronic pain – key considerations for appropriate physical therapy management - Courtney, Carol A. (J Man Manip Ther, 2017)
In last decades, knowledge of nociceptive pain mechanisms has expanded rapidly. The use of quantitative sensory testing has provided evidence that peripheral and central sensitization mechanisms play a relevant role in localized and widespread chronic pain syndromes. In fact, almost any patient suffering with a chronic pain condition will demonstrate impairments in the central nervous system. In addition, it is accepted that pain is associated with different types of trigger factors including social, physiological, and psychological. This rational has provoked a change in the understanding of potential mechanisms of manual therapies, changing from a biomechanical/medical viewpoint, to a neurophysiological/nociceptive viewpoint. Therefore, interventions for patients with chronic pain should be applied based on current knowledge of nociceptive mechanisms since determining potential drivers of the sensitization process is critical for effective management. The current paper reviews mechanisms of chronic pain from a clinical and neurophysiological point of view and summarizes key messages for clinicians for proper management of individuals with chronic pain.